2019
DOI: 10.1017/s1431927618015581
|View full text |Cite
|
Sign up to set email alerts
|

Atom Probe Tomography Interlaboratory Study on Clustering Analysis in Experimental Data Using the Maximum Separation Distance Approach

Abstract: We summarize the findings from an interlaboratory study conducted between ten international research groups and investigate the use of the commonly used maximum separation distance and local concentration thresholding methods for solute clustering quantification. The study objectives are: to bring clarity to the range of applicability of the methods; identify existing and/or needed modifications; and interpretation of past published data. Participants collected experimental data from a proton-irradiated 304 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 52 publications
(64 reference statements)
1
16
0
Order By: Relevance
“…In zircon, several studies have reported the presence of clusters of Y, Pb and Al (Valley et al , , Peterman et al , Piazolo et al , Blum et al , Peterman et al ). Isolation of these clusters, using 3D volumes defined by isoconcentration surfaces (Hellman et al ) or cluster analysis routines (e.g., Stephenson et al , Dong et al ), significantly reduces the analytical background and permits quantification of compositional and isotopic analysis of these clusters. 207 Pb/ 206 Pb measurements of clusters in both concordant and discordant zircon (Figure ) have been shown to be distinct from bulk isotopic compositions outside the cluster and this has allowed the isotopic compositions of the clusters to be used to constrain the timing of geological events (Valley et al , , Peterman et al ).…”
Section: Geoscience Applicationsmentioning
confidence: 99%
“…In zircon, several studies have reported the presence of clusters of Y, Pb and Al (Valley et al , , Peterman et al , Piazolo et al , Blum et al , Peterman et al ). Isolation of these clusters, using 3D volumes defined by isoconcentration surfaces (Hellman et al ) or cluster analysis routines (e.g., Stephenson et al , Dong et al ), significantly reduces the analytical background and permits quantification of compositional and isotopic analysis of these clusters. 207 Pb/ 206 Pb measurements of clusters in both concordant and discordant zircon (Figure ) have been shown to be distinct from bulk isotopic compositions outside the cluster and this has allowed the isotopic compositions of the clusters to be used to constrain the timing of geological events (Valley et al , , Peterman et al ).…”
Section: Geoscience Applicationsmentioning
confidence: 99%
“…It is informative to compare the estimates in Table 4 to estimates of the same parameters using the MSA, which is one of the most commonly used cluster identification tools in the APT community [12,13,14]. The MSA requires two user-defined input parameters: d max , the maximum distance between two points in a cluster, and N min , the minimum number of points in a cluster [13].…”
Section: Comparison To Maximum Separation Algorithmmentioning
confidence: 99%
“…For example, the maximum separation algorithm (MSA), one of the most commonly used cluster detection algorithms in the APT community, requires the initialization of two crucial parameters: d max (the maximum distance between two points in a cluster) and N min (the minimum number of points in a cluster) [12]. This algorithm's output is highly sensitive to the choice of these two parameters [13,14], and while there are general guidelines for this parameter selection [10,12], the procedures are still subjective. This user-guided parameter selection is typical of other cluster detection algorithms as well [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we selected the maximum separation method (MSM) as an example to implement the methodology, because the MSM, embedded in the IVAS software, is widely used for cluster identification in the APT community and suitable for analyzing clusters in a dilute alloy (Hyde et al, 2011a;Dong et al, 2019). The basic idea is not confined to the MSM, but is applicable to all other cluster search algorithms, as long as the spacing information of the identified clusters is carefully extracted and registered.…”
Section: Introductionmentioning
confidence: 99%
“…With such information, we can systemically investigate the size and population evolution of these clusters (in comparison with other isolated clusters) with different aging conditions and address the clusters in coalescence using the ex situ technique. In this study, we selected the maximum separation method (MSM) as an example to implement the methodology, because the MSM, embedded in the IVAS software, is widely used for cluster identification in the APT community and suitable for analyzing clusters in a dilute alloy (Hyde et al, 2011 a ; Dong et al, 2019). The basic idea is not confined to the MSM, but is applicable to all other cluster search algorithms, as long as the spacing information of the identified clusters is carefully extracted and registered.…”
Section: Introductionmentioning
confidence: 99%